2019
DOI: 10.1097/rlu.0000000000002610
|View full text |Cite
|
Sign up to set email alerts
|

18F-FACBC PET/MRI in Diagnostic Assessment and Neurosurgery of Gliomas

Abstract: Purpose: This pilot study aimed to evaluate the amino acid tracer 18 F-FACBC with simultaneous PET/MRI in diagnostic assessment and neurosurgery of gliomas. Materials and Methods: Eleven patients with suspected primary or recurrent low-or high-grade glioma received an 18 F-FACBC PET/MRI examination before surgery. PET and MRI were used for diagnostic assessment, and for guiding tumor resection and histopathological tissue sampling. PET uptake, tumor-to-background ratios (TBRs), time-activity curves, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 44 publications
5
35
2
Order By: Relevance
“…The results of this study show that 18 F-FACBC could provide useful information with regard to tumour detection. In particular, there was low 18 F-FACBC tracer uptake (SUV bkg ) in healthy brain tissue as well as high tracer uptake (SUV peak and SUV max ) (Tables 2 and 3 ) in both cerebral and cerebellar tumour VOIs, consistent with previous studies on gliomas (Bogsrud et al 2019 ; Karlberg et al 2017 ; Karlberg et al 2019 ; Tsuyuguchi et al 2017 ; Michaud et al 2020 ). We reported an increase in 18 F-FACBC uptake in healthy brain tissue (SUV bkg ) after radiation therapy in scan 2 (Table 2 ), but regardless of this increase, the distinctively low 18 F-FACBC tracer uptake in healthy tissue (SUV bkg ) played a large role in the high tumour contrast (TBR max and TBR peak ) in this patient.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results of this study show that 18 F-FACBC could provide useful information with regard to tumour detection. In particular, there was low 18 F-FACBC tracer uptake (SUV bkg ) in healthy brain tissue as well as high tracer uptake (SUV peak and SUV max ) (Tables 2 and 3 ) in both cerebral and cerebellar tumour VOIs, consistent with previous studies on gliomas (Bogsrud et al 2019 ; Karlberg et al 2017 ; Karlberg et al 2019 ; Tsuyuguchi et al 2017 ; Michaud et al 2020 ). We reported an increase in 18 F-FACBC uptake in healthy brain tissue (SUV bkg ) after radiation therapy in scan 2 (Table 2 ), but regardless of this increase, the distinctively low 18 F-FACBC tracer uptake in healthy tissue (SUV bkg ) played a large role in the high tumour contrast (TBR max and TBR peak ) in this patient.…”
Section: Discussionsupporting
confidence: 88%
“…However, MRI has some limitations, such as micro-metastasis detection, lesion boundary delineation and discrimination between progression and pseudo-progression after treatment (Bogsrud et al 2019 ). Dynamic and static data acquired from amino acid (AA) positron emission tomography (PET) could provide the opportunity for a more detailed analysis of brain tumour extent and malignancy (Karlberg et al 2017 ; Karlberg et al 2019 ). Additionally, AA PET has been shown to detect malignant glioma progression as well as treatment efficacy earlier than MRI (Galldiks et al 2013 ; Unterrainer et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has only limited clinical value in neuro-oncology due to the poor contrast between neoplastic and normal brain tissue. In contrast to 18 F-FDG uptake, protein metabolism is clearly elevated in brain tumor cells compared to healthy brain tissue, making radiolabeled amino acids, such as [ 11 C]-methyl-L-methionine ( 11 C-MET), O -(2-[ 18 F]fluoroethyl)-L-tyrosine ( 18 F-FET), 3,4-dihydroxy-6-[ 18 F]-fluoro-L-phenylalanine ( 18 F-FDOPA), or 18 F-fluciclovine ( 18 F-FACBC) important targets for brain tumor imaging [ 3 , 4 , 5 ]. In correspondence to its increased availability, a high number of studies, including multicenter trials, have shown that amino acid PET (AA-PET) provides additional information on the metabolic properties of brain tumors.…”
Section: Introductionmentioning
confidence: 99%